Evaluation of Electrolyte Imbalance on Intensive Care Unit Admission and Its Effect on Prognosis - Erbil Türksal; Esra Özayar; Adem Selvi; Merve Karaşahin; Esra Onhan Tekoğlu; Ali Koç (Galenos Yayinevi, 2024)
Objective: Electrolyte imbalance is an important factor that is frequently observed in the ICU and affects prognosis. We analyzed the type of electrolyte imbalance on ICU admissions and its relation to prognosis, mechanical ventilation day, ICU and hospital stay, and mortality. Materials and Methods: The electrolyte values of 826 patients admitted to the ICU were analyzed. Demographic data, the type of electrolyte imbalance, mechanical ventilation day, length of stay in the ICU and hospital, APACHE-II scores, and mortality status were recorded. Results: A total of 826 patients were included. Of the patients, 252(30.5%) had dysnatremia, 193 (23%) had dyskalemia, 432 (52%) had dyscalcemia, 389 (47%) had dysmagnesaemia, and 625 (75%) had dysphosphatemia. APACHE-II score, mechanical ventilation day, and length of stay in ICU and hospital were significantly higher in hypernatremia than in normonatremia and hyponatremia. In hypokalemia, the length of stay in the ICU and mechanical ventilation day was significantly higher than in normokalemia. The mortality rate was 1.7 and 4.4 times higher in hyponatremia and hypernatremia, respectively, than in normonatremia. Mortality was 1.8 times higher in hypokalemia and 2.2 times higher in hyperkalemia than in normokalemia. Mortality was 11 times higher in hypercalcemia than in normocalcemia. Conclusion: Electrolyte imbalance is frequently observed among ICU patients. In particular, in patients with dysnatremia and dyskalemia, the prognosis is worse.